Publicistic articles on the pages of the 'Sovet Әdәbiaty' ('Sovetskaya Literatura') journal in the end of the Stalin era - I.F. Fattakhov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper is devoted to the study of the Tatar publicism during the end of the Stalin era based on the analysis of the monthly literary and socio-political journal “Sovetskaya Literatura” (“Soviet Literature”), the printed edition of the Union of Writers of Tatarstan of the Tatar Autonomous Soviet Socialist Republic. The publicistic activity of the following persons has been considered: Tatar writers – Gazi Kashshaf, Garif Gubay, Naki Isanbet; scientists – Khatip Guzman, Mukhamet Gainullin; statesman – Salih Batyev. As a result of the research, a number of conclusions have been made: firstly, the government worked closely with the national intelligentsia; secondly, the published materials undoubtedly reflected the policy of the state, they clearly expressed the spirit of Stalinism, but the editorial board and the editor, G. Kashshafa, managed to balance the pathway of the journal and put the national issues at the forefront of the development of the literary process. The purpose of the study is determined by the fact that it is necessary to analyze the state of Tatar journalism of that period. To achieve this purpose, the methods of historical and descriptive analysis have been used. The paper is of scientific value in terms of identifying the position of Russian journalism at the national and regional levels within the global information space. The practical value of the research is that it provides an opportunity to investigate the problem in detail. It has been concluded that the “Sovetskaya Literatura” journal, similarly to all Soviet printed editions, was strongly influenced by the party ideology. The authorities closely cooperated with the intelligentsia, and literature and art turned out to be the powerful tools of the Soviet government and strengthened J.V. Stalin's dictatorship. The authorities controlled everything. The materials submitted for publication were edited by political censors; they clearly expressed the spirit of Stalinism, the cult of J.V. Stalin's personality. Every issue of the journal had the “Publicism” section. The research demonstrates that the responsible editor of the journal, G. Kashshaf, revived the departments of journalism and criticism, the Tatar journalism on the pages of the journal was carefully corrected by the censors and imbued with the spirit of the Stalin era.